Trial protocol of an open label pilot study of lisdexamfetamine for the treatment of acute methamphetamine withdrawal. - Liam S Acheson; Nadine Ezard; Nicholas Lintzeris; Adrian Dunlop; Jonathan Brett; Craig Rodgers; Anthony Gill; Michael Christmass; Rebecca McKetin; Michael Farrell; Steve Shoptaw; Krista J Siefried (PLoS ONE, 2022)
Introduction Methamphetamine (MA) use disorder is an important public health concern. MA withdrawal is often the first step in ceasing or reducing use. There are no evidence-based withdrawal treatments, and no medication is approved for the treatment of MA withdrawal. Lisdexamfetamine (LDX) dimesilate, used in the treatment of attention deficit hyperactivity disorder and binge eating disorder has the potential as an agonist therapy to ameliorate withdrawal symptoms, and improve outcomes for patients. Methods A single arm, open-label pilot study to test the safety and feasibility of LDX for the treatment of MA withdrawal. Participants will be inpatients in a drug and alcohol withdrawal unit, and will receive a tapering dose of LDX over five days: 250mg LDX on Day 1, reducing by 50mg per day to 50mg on Day 5. Optional inpatient Days 6 and 7 will allow for participants to transition to ongoing treatment. Participants will be followed-up on Days 14, 21 and 28. All participants will also receive standard inpatient withdrawal care. The primary outcomes are safety (measured by adverse events, changes in vital signs, changes in suicidality and psychosis) and feasibility (the time taken to enrol the sample, proportion of screen / pre-screen failures). Secondary outcomes are acceptability (treatment satisfaction questionnaire, medication adherence, concomitant medications, qualitative interviews), retention to protocol (proportion retained to primary and secondary endpoints), changes in withdrawal symptoms (Amphetamine Withdrawal Questionnaire) and craving for MA (visual analogue scale), and sleep outcomes (continuous actigraphy and daily sleep diary). Discussion This is the first study to assess lisdexamfetamine for the treatment of acute MA withdrawal. If safe and feasible results will go to informing the development of multi-centre randomised controlled trials to determine the efficacy of the intervention.